Pendampingan Pemupukan Bayam Brazil Dengan Eco Enzyme Dengan Keseimbangan Bahan Sesuai Pola Matematika Di Desa Pulau Semambu Indralaya - Maya Puspita, Fitri; Octarina, Sisca; Yuliza, Evi; Hanum, Laila; Aryani, Robeah; Hernanda, Eggyana Deri (Jurnal Gema Ngabdi, 2024)
Brazilian spinach is a type of spinach that is very easy to cultivate and consume by the public because this plant is easy to plant and process and also has good health benefits when consumed. This mentoring activity, which is a community service activity regarding fertilizing Brazilian spinach, aims to provide maximum (optimal) harvest results using eco enzyme techniques that are appropriate to the dosage in the soil and plants with the concept of mathematical models. Eco Enzyme (EE) is a fermentation in the form of a multi-purpose liquid that comes from kitchen waste or organic waste such as fruit peels, vegetables and other food waste. EE can be used as an environmentally friendly fertilizer because this liquid can function as soil and plant fertilizer, eliminate pests, and can improve the quality of vegetables or fruit. Therefore, the selection of EE as fertilizer for Brazilian spinach plants with a balance of ingredients is in accordance with the mathematical model carried out in community service